2020
DOI: 10.1016/j.btre.2020.e00557
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of cordycepin in Ophiocordyceps sinensis using growth supplements under submerged conditions

Abstract: Highlights The growth supplements remarkably enhanced the cordycepin production. Hypoxanthine and adenosine yielded higher amount of cordycepin. The potent growth supplements activated cordycepin biosynthesis pathway. Upregulation of RNR , NT5E , ADEK and purA mRNA expression was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Thus, it can be expected that the obtaining of industrial strains possesses salt tolerance and high cordycepin production via overexpression of the cordycepin biosynthetic gene and salt-tolerant gene. Interestingly, a significant upregulation of ribonucleotide reductase (RNR, 70.19-fold), 5′-Nucleotidase ( NT5E , 63.43-fold), purA (Adenylosuccinate synthase, 8.43-fold), and Adenylate kinase ( ADEK , 17.52-fold) gene expression was observed upon hypoxanthine treatment, which are downstream genes responsible for cordycepin biosynthesis in Ophiocordyceps sinensis ( 30 ). Analogous effects have also been achieved on several other potent growth supplements, such as amino acids, plant hormones, and vitamins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be expected that the obtaining of industrial strains possesses salt tolerance and high cordycepin production via overexpression of the cordycepin biosynthetic gene and salt-tolerant gene. Interestingly, a significant upregulation of ribonucleotide reductase (RNR, 70.19-fold), 5′-Nucleotidase ( NT5E , 63.43-fold), purA (Adenylosuccinate synthase, 8.43-fold), and Adenylate kinase ( ADEK , 17.52-fold) gene expression was observed upon hypoxanthine treatment, which are downstream genes responsible for cordycepin biosynthesis in Ophiocordyceps sinensis ( 30 ). Analogous effects have also been achieved on several other potent growth supplements, such as amino acids, plant hormones, and vitamins.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, optimization of medium composition is usually the first choice to increase the content of cordycepin. Growth supplements and additives, such as sugar, amino acids (L-alanine, glycine, casein hydrolysate, and glutamine), vitamins, inorganic salts (ferrous sulfate and sodium selenite), nucleoside analog (hypoxanthine and adenosine), porcine liver extracts, or vegetable oils (peanut and cottonseed oil), were proved to be successful ( 8 , 25 30 ). Moreover, ways of genetic and metabolic engineering are noteworthy, and two main methods are mentioned as follows, the overexpression and disruption of the gene on the cordycepin biosynthetic cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The content of cordycepin was analyzed by RP-HPLC as described by Kaushik et al (2020) with some modifications [ 30 ]. The analysis was performed using a Hitachi HPLC system (Merck, Tokyo, Japan) equipped with a type L-7100 pump.…”
Section: Methodsmentioning
confidence: 99%
“…For example, researchers have investigated different media to artificially culture C. militaris mycelia, such as silkworm pupa, solid rice medium, germinated soybean medium, and soybean broth [ 34 39 ]. Many studies have investigated different concentrations of carbon and nitrogen in the media to explore the best conditions for the growth of C. militaris mycelia [ 40 45 ]. Previous studies have shown that C. militaris mycelia contain specific pharmacologically active components, such as cordycepin, polysaccharides, ergosterol, and mannitol, and that they can be used effectively for various medicinal purposes or as functional foods [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%